In vitro and in silico optimization of oral taxane therapy - van Eijk, Maarten (Utrecht University, 2023)
The taxanes, paclitaxel, docetaxel, and cabazitaxel, are essential in the treatment of various solid tumors. Oral formulations of these compounds are being developed, which can provide a more patient-friendly and cost-effective alternative to the common intravenous route of administration. This thesis describes several projects that were undertaken to optimize the treatment with these oral formulations. In the first chapters, we provide an overview of solid tumor types in which enzymes, that normally play a role in breaking down the taxanes in the liver and intestines, are present. We also show that these enzymes are a mechanism by which breast cancer cells become less sensitive to treatment with docetaxel, and that this may be overcome by adding specific enzyme inhibitors, like ritonavir, to treatment with docetaxel. In the second chapter, we demonstrate how mathematical models, that describe the behavior and the effect of oral taxanes in the body, can be used in their development. With these models, we were able to exclude genetic differences as a source for large variation in oral docetaxel plasma concentrations between patients. Additionally, we show that these models can be used to capture the effect of formulations on plasma concentrations of paclitaxel, and to predict a safe starting dose for first-in-human studies with oral cabazitaxel based on data from mice. The third chapter addresses how the administration route and schedule may affect treatment efficacy and toxicity. We conclude that a weekly docetaxel schedule reduces bone marrow toxicity compared to a three-weekly schedule. Moreover, an oral formulation optimizes exposure to docetaxel which may improve treatment efficacy. Taken together, these research efforts fill relevant knowledge gaps for the development of oral taxanes, which may ultimately lead to optimized treatment of patients with these formulations.
Keywords: docetaxel; paclitaxel; cabazitaxel; CYP3A; intratumoral; pharmacokinetic; pharmacodynamic; pharmacometric; schedule; SDG 3 - Good Health and Well-being